Characteristics of Photosynthetic Active Radiation (PAR) Through Statistical Analysis at Larnaca, Cyprus - Pashiardis, Stelios; Kalogirou, Soteris A.; Pelengaris, A. (My University, 2017)
Measurements of Photosynthetically Active Radiation (PAR) and global solar radiation at Larnaca (a coastal site in Cyprus) during the period 3013-2015 were used to investigate the seasonal characteristics of PAR and PAR/G ratio (PAR fraction or fFEC). PAR showed seasonal features with higher values in summer and lower values in winter. The annual mean values of PPFD and fFEC being 40.3 mol m-2 d-1 and 2.03 mol M J-1, respectively. Monthly average daily PAR increased from 19.1 mol m-2 d-1 (in December) to 59.6 mol m-2 d-1 (in June).The monthly daily average of fFEC remained almost constant throughout the year at Larnaca. The spatial variability of PAR was also investigated using measurements from other four sites with different climate characteristics. The annual mean daily PAR value ranged between 31.7 to 40.0mol m-2 d-1. The highest values are recorded in the coastal stations (Larnaca and Paralimni). The annual average value of fFEC at the five observation sites ranged from 1.82 mol MJ-1 to 2.03 mol MJ-1, in accordance to what is observed in most parts of the world. The highest appeared in the coastal sites of Larnaca and Paralimni due to the presence of high water vapour atmospheric concentrations. Elevation plays a significant role on the values of the above variables. As a general trend, fFEC followed the order Clear
Keywords: Photosynthetic active radiation; Statistical analysis; Temporal and spatial variation; Modelling PAR; Cyprus